A Long and a Short Leg Make for a Wobbly Equilibrium - Gârleanu, Nicolae; Panageas, Stavros; Zheng, Geoffery (American Economic Review, 2026)
We provide a model to explain how the interaction between the spot and lending markets for stocks can lead to abrupt changes in short selling activity. Furthermore, rational short sellers may choose to abandon the market even as mispricing widens. We document empirically that the dynamics of short selling are fat tailed and subject to abrupt changes, especially for the stocks that the model identifies as susceptible to such dynamics. (JEL G11, G12, G14, G41)